2020
DOI: 10.1037/sah0000172
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional self-forgiveness in firefighters predicts less help-seeking stigma and fewer mental health challenges.

Abstract: Firefighters face increased rates of mental health disorders secondary to traumatic exposure yet consistently report that stigma interferes with help-seeking. We examined whether firefighters who are by disposition more self-forgiving would exhibit less stigma and fewer mental health challenges. Dispositional self-forgiveness is a personality trait characterized by nonintropunitive responding, self-acceptance/positivity, and resolution of negative states following perceived failure. A community sample of profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Regarding PTSD rates, deviations were verified-while some studies reported PTSD rates of 26.6% [10] and 31.8% [11] among firefighters, others indicated 13% [12], or even 2.7% [13]. The reasons for a such variation in PTSD prevalence may be related to: the location of data collection, such as when it occurred inside fire departments-due to the lack of homogeneity in samples in relation to the risk faced or, when they are homogeneous, the workplace may inhibit the emotional manifestations [14]; cultural characteristics [15]; or fear of stigma, a common aspect among these professionals [16][17][18][19]. In addition to presenting evidence for the prevalence of PTSD, the symptoms recurrently mentioned by studies were depression (N = 16), alcohol abuse (N = 11), suicidal ideation or behaviors (N = 10) and avoidance (N = 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding PTSD rates, deviations were verified-while some studies reported PTSD rates of 26.6% [10] and 31.8% [11] among firefighters, others indicated 13% [12], or even 2.7% [13]. The reasons for a such variation in PTSD prevalence may be related to: the location of data collection, such as when it occurred inside fire departments-due to the lack of homogeneity in samples in relation to the risk faced or, when they are homogeneous, the workplace may inhibit the emotional manifestations [14]; cultural characteristics [15]; or fear of stigma, a common aspect among these professionals [16][17][18][19]. In addition to presenting evidence for the prevalence of PTSD, the symptoms recurrently mentioned by studies were depression (N = 16), alcohol abuse (N = 11), suicidal ideation or behaviors (N = 10) and avoidance (N = 6).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the severity and exposure time enter in this model, since trauma load [10,45] and the number of critical incidents [14,25,31] were significantly related to PTSD symptom severity (both p range <0.01 to <0.001). Notably, personality traits such as extraversion (p <0.001) [40], impulsivity (p = 0.003) [21], optimism (p <0.05) [40], self-forgiveness (p <0.001) [18], distress tolerance ( p<0.001) [50], and resiliency (p <0.001) [24,33,55] seem to affect all other variables which influence the perception of stress, thereby affecting the choice of coping strategies. Moreover, personality traits were directly associated with the choice of coping strategies (p range <0.05 to <0.001) [21,36,40,44], which can lead to either stress-related diseases or normal stress reactions and a recovery process.…”
Section: A Relational Model For Stress In Firefightersmentioning
confidence: 99%
“…Sixth, the study did not take into consideration other potential mental health issues of the respondents, drug and alcohol use and other adverse experiences, e.g., those from the childhood. They might potentially increase the reported levels of PTSD symptomatology [ 11 , 26 – 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among risk factors against PTSD among firefighters, there are maladaptative coping styles [ 11 15 ], alienation, feelings of insecurity and lack of personal control [ 16 ], high neuroticism, and fear of dying on duty [ 17 ], anxiety sensitivity [ 18 , 19 ], negative emotionality [ 20 ], burnout [ 21 , 22 ], length of service and lower rank [ 10 , 14 , 23 25 ], previous high exposure to traumatic events and previous psychopathology [ 11 , 26 – 29 ], elevated startle response [ 30 ], increased tendency to catastrophize [ 31 ], high hostility and low self-efficacy [ 3 ], negative self-appraisals [ 14 , 32 ], occupational stress, lack of social support and shift work [ 10 , 33 35 ], external locus of control in the workplace, low education and low resilience [ 24 , 36 ], and high social introversion and masculinity [ 37 ]. These risk factors seem to fall into three broad categories—intrapersonal [ 11 22 , 27 31 , 36 ], workplace-related [ 10 , 11 , 14 , 23 – 26 ] and social [ 10 , 16 , 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forgiveness is the process of changing one's feelings and attitudes, including anger and revenge, after a negative experience (Barcaccia et al, 2018). Previous studies have revealed that forgiveness has the effect of reducing negative emotions (Roxas et al, 2019;Carpenter et al, 2020). Researchers also found that forgiveness provides justice among individuals, reduces anxiety and depression, and increases well-being (Steiner et al, 2012;Fincham, 2015).…”
Section: The Mediator Role Of Forgivenessmentioning
confidence: 99%